Spatial Assessment of Flash Flood Susceptibility in a Steep Tropical Watershed: The Banyuputih Case Study, Indonesia - Gandhi Teguh Lesmana; Entin Hidayah; Retno Utami Agung Wiyono; Fidyasari Kusuma Putri; Hilma Wasilah Robbani; Jagat Adi Samudra (Journal of Applied Geospatial Information, 2026)
Flash flood susceptibility in upstream watersheds is influenced not only by rainfall intensity but also by the spatial configuration of physiographic characteristics and land use. The Banyuputih Watershed in East Java has experienced recurrent flash floods, emphasizing the need for spatial assessment to support effective mitigation planning. This study develops a flash flood susceptibility map using a GIS-based multi-criteria approach integrated with logistic regression. The analyzed factors include DEM-derived topographic parameters (elevation, slope, Topographic Position Index (TPI), Topographic Wetness Index (TWI), and plan curvature), Hydrologic Soil Group (HSG), rainfall, river density, land cover, and NDVI. The relative influence of each factor was determined from logistic regression coefficients. The results classify the watershed into five susceptibility levels: very low, low, moderate, high, and very high. High to very high susceptibility zones are spatially limited and mainly concentrated in upstream and parts of midstream areas characterized by flow-convergent topography and less protective land cover. Most of the watershed is dominated by very low to moderate vulnerability, indicating that flash flood potential is spatially localized. The resulting map provides a scientific basis for watershed management, land-use planning, and targeted nature-based mitigation strategies.